Late presentation biliary atresia at the Chris Hani Baragwaneth Hospital: a retrospective study - Moreke, Refiloe Relebohile (My University, 2020)
BACKGROUND: Biliary atresia (BA) is a destructive inflammatory obliterative cholangiopathy, which if untreated, can lead to liver cirrhosis and death by age of 2 years. Surgical intervention is the only therapy that improves prognosis if performed at < 90 days. In affluent countries, liver transplantation has improved outcomes in children with BA. In limited resource settings, Kasai hepatoportoenterostomy (KPE) remains the standard of care for children with biliary atresia. OBJECTIVES: To identify and describe the subgroup of infants with BA who were 90 days or older at presentation and to identify factors contributing to the late presentation and document the management and outcomes of these children. METHODS: All infants diagnosed with BA at Chris Hani Baragwanath Academic Hospital (CHBAH) between January 2010 and December 2015 were included in the study. Presenting signs and symptoms were compared between early and late presenters. Parental and medical factors contributing to late presentation were investigated. Management and outcomes of the late presenters were recorded. RESULTS: BA was diagnosed in 122 infants during the study period. Of the 102 cases analysed, 49 (48%) were identified as late presenters, with a median age at presentation of 3) 172 days (IQR 119.5; 193.5). Both parental and medical factors contributed to late presentation. Parental factors primarily related to inability to recognize persistence of jaundice as abnormal. Factors at all levels of health care included lack of awareness of significance of prolonged jaundice of greater than 14 days and misdiagnosis of the condition. Of the 49 late presenters, 13 were offered laparotomy, with KPE performed on 10 of these patients. Clearance of jaundice at 6 month post KPE was only documented in 2 patients. Six of the 49 patients were referred for liver transplantation. Of these 1 was transplanted, and 4 were listed, of which 3 demised while on the waiting list and 1 was waiting to be listed. As of January 2017, 10 patients were still alive, 12 known to have demised and the rest were lost to follow up. CONCLUSION: Nearly half of our patients presented late. Both parental and medical factors contribute to the late presentation of patients with BA. We advocate for educating the community and medical personnel of the detrimental effect of late presentation of BA. Increased awareness is essential, as only a handful of late presenters can be offered KPE and or liver transplantation.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Medicine in Paediatrics to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2019